Performance of an innovative self-centering buckling restrained brace for mitigating seismic responses of bridge structures with double-column piers. (1st October 2017) - Dong, Huihui; Du, Xiuli; Han, Qiang; Hao, Hong; Bi, Kaiming; Wang, Xiaoqiang
Highlights: Development of a novel SC-BRB consisting of a self-centering system and a BRB system. Large-scale experimental studies of the SC-BRB. Application of the SC-BRB in RC double-column bridge pier for seismic retrofitting. Abstract: Buckling restrained braces (BRBs) are normally incorporated in the beam-column structures to serve as energy dissipation members due to their stable hysteretic behavior. However, the structures equipped with BRBs may suffer excessive residual deformations when they are subjected to large earthquakes. To minimize the residual deformations of the structures with traditional BRBs, a novel self-centering buckling restrained brace (SC-BRB) consisting of a self-centering system and a traditional BRB system is developed in the present study. Large-scale experimental studies are carried out and the hysteretic behavior of the proposed system is compared with the traditional BRB and self-centering brace (SCB). Experimental results show that the SC-BRB exhibits flag-shaped hysteresis response with a small residual deformation and a moderate energy dissipation capability. The proposed SC-BRB is applied to a reinforced concrete (RC) double-column bridge pier for seismic retrofitting. Nonlinear dynamic analyses are carried out to examine its effect on the seismic behavior of the bridge. Numerical results demonstrate that the bridge equipped with SC-BRB system shows much smaller residual displacement compared to the ones equipped with traditional BRB and SCB systems. Numerical results also indicate that SC-BRB system tends to amplify the peak acceleration of the bridge.